2007
DOI: 10.1158/1078-0432.ccr-06-1746
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Fibroblast Activation Protein in Patients with Colon Cancer

Abstract: Purpose: Human fibroblast activation protein (FAP)/seprase is a 97-kDa surface glycoprotein expressed on tumor associated fibroblasts in the majority of epithelial cancers including colon adenocarcinomas. FAP overexpression in human tumor cells has been shown to promote tumor growth in animal models, and clinical trials targeting FAP enzymatic activity have been initiated. The primary objective of this study was to evaluate the clinical significance of stromal FAP in human colon cancers by immunohistochemisty.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
246
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(266 citation statements)
references
References 27 publications
16
246
2
2
Order By: Relevance
“…Moreover, this marker is upregulated when mesenchymal stem cells are recruited into growing tumors [21,22]. Tumor-associated stromal expression of FAP was found to be associated with more aggressive disease progression, and potential development of metastasis, recurrence, and death in colon and pancreatic cancers [23][24][25]. Previous studies in ovarian cancers treated with standard surgery followed by chemotherapy showed an association of FAP with advanced stage disease, lymph node metastasis, omental involvement, lymphovascular disease, and increased angiogenesis, but there is lack of data on the association of FAP with patient outcomes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this marker is upregulated when mesenchymal stem cells are recruited into growing tumors [21,22]. Tumor-associated stromal expression of FAP was found to be associated with more aggressive disease progression, and potential development of metastasis, recurrence, and death in colon and pancreatic cancers [23][24][25]. Previous studies in ovarian cancers treated with standard surgery followed by chemotherapy showed an association of FAP with advanced stage disease, lymph node metastasis, omental involvement, lymphovascular disease, and increased angiogenesis, but there is lack of data on the association of FAP with patient outcomes [26].…”
Section: Discussionmentioning
confidence: 99%
“…FAP immunostaining in fibroblasts was evaluated in CRC and in close vicinity to colonic epithelial cells in normal mucosa, hyperplastic polyps, and adenomas. Stromal staining was assessed as negative, ϩ, ϩϩ, or ϩϩϩ, according to the semiquantitative scale suggested by Henry et al 13 The ϩ, ϩϩ and ϩϩϩ categories were considered to be positive for FAP staining. Occasional epithelial staining was not analyzed.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…9 It is normally expressed transiently in healing wounds, and abundantly by activated stromal fibroblasts in CRC and other human epithelial malignancies (breast, lung, and ovary carcinomas). 10 -12 Abundant FAP expression has been implicated as a negative prognostic factor in patients with metastatic CRC, 13 but its biological role is still not clear. However, a clinical trial on CRC patients using talabostat, an inhibitor of FAP-enzymatic activity, showed a minimal clinical effect, and the authors suggest that the partial inhibition may be due to another contributing factor or factors.…”
mentioning
confidence: 99%
“…9 FAP is expressed infrequently on the colon cancer cells themselves, and stromal cells residing in colorectal adenomas are also predominantly FAP negative, suggesting that malignancy is required for effective FAP stromal induction. 10 Given its ubiquitous expression in both primary and metastatic colorectal carcinomas, FAP has been targeted by monoclonal antibodies, 11 but these non-inhibitory antibodies did not show clinical activity.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In a phase I trial of Val-boroPro in patients receiving myelosuppressive chemotherapy, the maximum tolerated dose was not reached up to 1200 μg per day, although orthostatic hypotension was observed at 800 μg per day. 19 Given the robust expression of FAP in the colorectal cancer stroma, 9 studies suggesting FAP portends a worse prognosis, 9 and preliminary evidence of Val-boroPro clinical activity in other clinical settings, [20][21][22] we conducted a phase II trial to evaluate the efficacy and safety of Val-boroPro monotherapy in patients with metastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%